Mark Bradford: A política entre o Corpo e o Espaço - Rigatti, André Luiz (Farol, 2022)
This paper seeks to understand some central poetic elements in the work of the American artist Mark Bradford (USA, 1961), situated between political positions that strain senses of body and space. As well as seeking to elucidate how these meanings are perceived along its trajectory as social engagements and political reflections of our contemporary society, having the practice of painting as a place for such positions. Some paintings in particular and individual exhibitions by the artist will be analyzed, such as those held in 2021 at the Serralves Museum of Contemporary Art, in Porto, Portugal and his participation as a representative of the United States of America in the 57th Venice Art Biennale in 2017.